Secure online testing system for LMS moodle - Vahe A. Arakelyan (АН Арм. ССР)
In recent years e-learning systems have widely been used, which raised some security issues. One of these issues is the problem of providing secure online testings, quizzes and exams. Usually such problems are resolved with specially equipped exam-rooms. In Armenia providing such exam-rooms to large number of students is an expensive solution. In this paper an application of new environment is proposed and described, which will make possible to use other computers. The idea is to lock down the students' computers, so during the exam they have no opportunity to use the internet, external memory cards, ¯les located on computer`s HDDs or other sources of information. There is no need to have big test-rooms with expensive equipment, when using this environment. An online exam environment is developed, which ensures secure online testing from the students' computers, so that no local program or information can be used during the exam. The system operates independently of computer's operation system, without making any program changes.
Keywords: Mathematics